Isotopic Characterization of Precipitation, Inflow, and Outflow of Lake Toba as a First Assessment of Lake Water Balance Study - P. Sidauruk; B. Pratikno; E. R. Pujiindiyati (Atom Indonesia, 2018)
Isotopic characterization of all identified hydrological units in Lake Toba such as precipitation, inflows, outflows, and lake water, as a first assessment of lake water balance study, has been conducted. The isotopic characterization was done through the interpretation of the relationship of dD and  d18O values of collected samples from various water sources and their variations as a function of time and space. Rain water samples were collected from four rain collectors that were installed in the study area in a monthly sampling for a period of 12 months in 2014. Several samples from various water sources i.e., inflow streams, outflows, springs, and lake water, were also collected 2-3 times during this sampling period. From monthly sampling of rain water, local meteoric water line (LMWL) and the equation of elevations versus dD values have been constructed. Due to the slightly higher temperature in the study area compared with the average temperature on the other parts of the world, the slope of the constructed LMWL is slightly less than the slope of global meteoric water line. Based on the equation of elevations versus dD values, the elevations of four springs around study area have been identified. From the linear relationship of dD and  d18O values of collected samples from inflow streams, it was found that most of the samples have experienced evaporation process before entering the lake. Due to mixing with other surface water and longer transit time, the dD and  d18O values of those samples from streams in the Sumatran side are more enriched than those samples from streams in the Samosir side. It was also found that lake water has experienced significant evaporation as indicated by the dD and  d18O values that were more enriched than any other samples. The dD and  d18O of Asahan River samples, the only output of Lake Toba, were found to be very close to the dD and  d18O of the lake. This is because almost all water that flowed in Asahan River originated from the lake.